2021
DOI: 10.1016/j.str.2021.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for accommodation of emerging B.1.351 and B.1.1.7 variants by two potent SARS-CoV-2 neutralizing antibodies

Abstract: Emerging SARS-CoV-2 strains, B.1.1.7 and B.1.351, from the UK and South Africa, respectively, show decreased neutralization by monoclonal antibodies and convalescent or vaccinee sera raised against the original wild-type virus, and are thus of clinical concern. However, the neutralization potency of two antibodies, 1–57 and 2–7, which target the receptor-binding domain (RBD) of the spike, was unaffected by these emerging strains. Here, we report cryo-EM structures of 1–57 and 2–7 in complex with spike, reveali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…Class IV antibodies, e.g. 1-57, 2-7, S309 and BD-812, hold the greatest potential for harboring ultra-potent neutralization activity and markedly high tolerance to most VOCs (63,67). Not surprisingly, all class IV antibodies, but CV07-270, exhibited excellent neutralizing breadth and potency to VOCs (Fig.…”
Section: Main Textmentioning
confidence: 94%
“…Class IV antibodies, e.g. 1-57, 2-7, S309 and BD-812, hold the greatest potential for harboring ultra-potent neutralization activity and markedly high tolerance to most VOCs (63,67). Not surprisingly, all class IV antibodies, but CV07-270, exhibited excellent neutralizing breadth and potency to VOCs (Fig.…”
Section: Main Textmentioning
confidence: 94%
“…Despite its proximity to the epitope, however, 484 do not interact significantly with Fab 1-57. Structural modeling of the E484K mutation showed that the K484 residue was geometrically compatible with Fab 1-57 binding at serine 29 with a hydrogen bond (57). Interaction of wild-type RBD by antibody Fab 2-7 is dominated by connection proximal to the RBD loops formed by residues 438-451 and 495-502.…”
Section: Class 1 Antibodiesmentioning
confidence: 99%
“…Another Class I mAbs of interest are monoclonal antibodies Fab 1-57 and Fab 2-7 which bind to the RBD epitope outside the hotspot of evolutionary pressure (57). Recognition of wild-type RBD by Fab 1-57 is dominated by the heavy chain, which buries 533.7 Å surface area, with a minor 223.3 Å contribution by the light chain.…”
Section: Class 1 Antibodiesmentioning
confidence: 99%
“…Emerging viral variants that exhibit increased infectivity and virulence emphasize the need for continued improvement in immunization and therapeutic approaches. Specifically, the B.1.1.7 (UK), B.1.351 (South Africa), P.1 (Brazil), and other strains demand careful attention ( 9 , 10 , 11 , 12 , 13 , 14 ). Exploring the detailed structures of anti-viral antibodies can provide critical understanding of means to attenuate viral adsorption and entry, and to prevent or retard ongoing infection and communal spread.…”
Section: Introductionmentioning
confidence: 99%